The development of long-term care in post-socialist member states of the EU - Stanislawa Golinowska; Agnieszka Sowa (Center for Social and Economic Research (CASE), 2013)
Long-term care (LTC) in the new EU member states, which used to belong to the former socialist countries, is not yet a legally separated sector of social security. However, the ageing dynamics are more intensive in these states than in the old EU member states. This paper analyses the process of creating an LTC sector in the context of institutional reforms of social protection systems during the transition period. The authors explain LTC's position straddling the health and social sectors, the underdevelopment of formal LTC, and the current policies regarding the risk of LTC dependency. The paper is based mainly on the analysis of information provided by country experts in the ANCIEN project.
Keywords: I18; I31; J11; J18; 330; Labor market; social policy and social services; Europe; long-term care; social sector reform; social policy; Langzeitpflege; Soziale Sicherheit; Sozialpolitik; Alternde Bevölkerung; Familienpflege; Systemtransformation; EU-Mitgliedschaft